Theoretical Electrochemical Study and Calculation of Free Energies of Electron Transfer in B-Cyclodextrins/Fullerenes C60 Nanostructure Complexes - Farasati Far, Bahareh; Naimi-Jamal, Mohammad Reza; Rizehbandi, Mohammad; Mehboob, Muhammad Yasir (Journal of Composites and Compounds, 2023)
Cyclodextrin is a cyclic molecule that contains the three essential six, seven, and eight glucose molecules, called by the names a, B, and y-cyclodextrin, individually. Cyclodextrins compounds are thought to be completely polar as a result of the hydroxyl groups present in glucose moieties. Secondary C2-hydroxyl groups of glucose units are found on the secondary face, while the C6-hydroxyl type groups are located on the primary face because these are related to the primary face of the incomplete cone. The C1 group, a glucoside oxygen ring, and another ring of C-H groups make up the inside of the cyclodextrin cone, making it rather nonpolar. Hydrophobic fullerenes compounds Cn [n= 60, 70, 76, 82, and 86] have been chosen for the guest molecules and different parameters like first to fourth free activations, the kinetic rate constant, the energies of electron transfer (ket(n)), and ?G#et(n) where (n=1-4), were calculated and discussed in detail. All the computed results showed the best coherence with the Marcus theory. Different analyses suggested that free energy is lowered due to an efficient electron transfer, which begins with the first step (the first of the four activate free energy values).